2019
DOI: 10.1016/j.concog.2019.102766
|View full text |Cite
|
Sign up to set email alerts
|

Systema Temporis: A time-based dimensional framework for consciousness and cognition

Abstract: This study uses a combined categorical-dimensional approach to depict a hierarchical framework for consciousness similar to, and contiguous with, factorial models of cognition (cf., intelligence). On the basis of the longstanding definition of time consciousness, the analysis employs a dimension of temporal extension, in the same manner that psychology has temporally organised memory (i.e., short-term, longterm, and long-lasting memories). By defining temporal extension in terms of the structure of time percep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…In fetuses older than 35 weeks of gestation, connections between regions known to belong to the DMN can already be observed (Thomason et al, 2015). This network is important for temporal awareness and integration of perceptual consciousness (Kent et al, 2019). This increase in connectivity can be seen as a driving factor to make conscious perception possible, e.g., when referring to the global workspace theory of consciousness (Baars, 1997; Dehaene et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fetuses older than 35 weeks of gestation, connections between regions known to belong to the DMN can already be observed (Thomason et al, 2015). This network is important for temporal awareness and integration of perceptual consciousness (Kent et al, 2019). This increase in connectivity can be seen as a driving factor to make conscious perception possible, e.g., when referring to the global workspace theory of consciousness (Baars, 1997; Dehaene et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For such a fine-grained concept of consciousness, the temporal scale on which an agent operates plays an important role. This has been developed further by Kent et al (2019), who place different concepts of consciousness on a logarithmic temporal scale – from conscious experience in the range of seconds to self-consciousness in the range of months. In the context of this finely differentiated view, it seems plausible that some more primary forms of consciousness emerge as early as during the fetal period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may reflect the nestedness of qualitative contents occurring at different temporal scales (Fingelkurts et al, 2010 ). Whether this necessitates a non-discrete mechanistic correlate in the brain remains a matter of contention (Fingelkurts et al, 2010 ; Kent et al, 2019 ; Winters, 2020 ; Kent and Wittmann, 2021 ). Nevertheless, contents are dynamic and consciousness seems to flow over an extended sense of the present (Poppel, 1997 ; Kent et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, most theoretical frameworks for consciousness limit the temporal aspects of consciousness to a few hundred ms timescales (Northoff and Lamme, 2020 ; Kent and Wittmann, 2021 ). Phenomenologically, it has been suggested that the experienced present moment is actually occurring over a wider temporal window in which the contents of consciousness are integrated (Poppel, 1997 ; Kent et al, 2019 ; Kent and Wittmann, 2021 ). A large number of studies have shown that the brain’s spontaneous activity during conscious states, prior to an experimental stimulus, is relevant to the resulting conscious content (Northoff and Huang, 2017 ).…”
Section: Introductionmentioning
confidence: 99%